Higher proportion of total and fat energy intake during the morning may reduce absolute intake of energy within the day. An observational study in free-living Japanese adults. (1st September 2015) - Tani, Yukako; Asakura, Keiko; Sasaki, Satoshi; Hirota, Naoko; Notsu, Akiko; Todoriki, Hidemi; Miura, Ayako; Fukui, Mitsuru; Date, Chigusa
Highlights: More proportion of energy intake in the morning reduces overall energy intake. Proportion of energy intake from fat has a great effect on overall energy intake. More energy intake in the morning reduces subsequent energy intake from meats. Abstract: Background: Although the distribution of energy intake throughout the day appears to impact overall daily energy intake, little is known about the ad libitum distribution of energy intake. Objective: Our aim was to investigate associations between the distribution of energy intake during the day and subsequent or overall energy intake, and food choice in free-living adults. Design: A total of 119 women and 116 men completed 16-day semi-weighed dietary records. The longitudinal dietary intake data for each participant were analyzed using a mixed model to examine the effect of energy intake at various times of day on subsequent or overall energy intake. Results: Mean proportion of total energy intake in the morning (4:00 a.m.–10:29 a.m.), afternoon (10:30 a.m.–4:59 p.m.) and evening (5:00 p.m.–3:59 a.m.) meal was 22.6%, 33.8% and 43.6% in men, and 24.7%, 36.5%, 38.8% in women, respectively. Proportion of energy intake (%) in the morning meal was significantly and negatively associated with energy intake (kcal) in the subsequent afternoon and evening meals, and consequently in the whole day in both sexes. This significant and negative association was also observed for proportion of energy intake (%) of fat, but not of carbohydrate or protein, in both sexes. Proportion of energy intake (%) in the morning meal was negatively associated with overall energy intake (kcal) from the group of meats, fish, and eggs in both sexes, and from the group of confectioneries and soft drinks in women. Conclusions: More energy in the morning meal may reduce energy intake, especially that from fat, in the subsequent meals, and consequently in the whole day.